On the calculation of integer sequences, associated with twin primes - Belovas, Igoris; Sabaliauskas, Martynas; Mykolaitis, Paulius (Lietuvos matematikos rinkinys, 2023)
The twin primes conjecture states that there are infinitely many twin primes. While studying this hypothesis, many important results were obtained, but the problem remains unsolved. In this work, the problem is studied from the side of experimental mathematics. Using the probabilistic Miller–Rabin primality test and parallel computing technologies, the distribution of prime pairs in the intervals (2n; 2n+1] is studied experimentally.